Modular (universal) CAR-T platforms in vivo: a comprehensive systematic review - Mohammad, Afraa; Yurina, Anna; Simonyan, Tatiana; Chistyakov, Daniil; Salman, Rand; Zornikova, Ksenia; Minina, Elizaveta; Bogolyubova, Apollinariya (Frontiers in Immunology, 2024)
BackgroundModular (universal) CAR T-platforms were developed to combat the limitations of traditional CAR-T therapy, allowing for multiple targeting of tumor-associated antigens and the ability to control CAR-T cell activity. The modular CAR-T platform consists of a universal receptor (signaling module) that recognizes an adapter molecule on the soluble module, which is responsible for antigen recognition. Multiple platforms have been developed over the last 12 years, and some of them have entered the clinical trial phase. This systematic review seeks to evaluate the different parameters of modular CAR-T platforms performance in animal models.MethodsA systematic search of literature in the PubMed database and in Google Scholar and BASE (Bielefeld Academic Search Engine) search engines was performed according to predefined eligibility criteria. All studies conducted on xenograft mouse models with any variant of modular CAR-T platforms were included. Forest plots were generated for visual presentation of the extracted quantitative findings (standardized mean difference (SMD) and median survival rate (MSR)).ResultsA total of 33 studies employing 15 different modular CAR-T platforms were included. The platforms varied in terms of CAR-T cells, soluble module doses, and their frequency of administration. The studies showed a reduction in tumor burden and in tumor volume compared to the combined negative group. In comparison with the positive control group, there was no significant change in tumor burden or volume. In all the included studies the experimental group had a higher survival probability compared to the combined negative group at the study endpoint, with no significant difference in survival rate compared to the positive control group.ConclusionThe modular CAR-T platforms are generally effective and are a valuable addition to the arsenal of CAR therapy.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/ PROSPERO, identifier CRD42023443984.